Histopathological features for coexistent invasive cancer in large colorectal adenomatous polyps. Issue 3 (16th June 2021) - Emmanuel, A; Haji, A; Gulati, S; Moorhead, J; Papagrigoriadis, S; Hayee, B; Diaz-Cano, S
Abstract: Background: Histopathological features associated with coexistent invasive adenocarcinoma in large colorectal adenomas have not been described. This study aimed to determine the association of histopathological features in areas of low-grade dysplasia with coexistent invasive adenocarcinoma. Methods: High-grade lesions (containing high-grade dysplasia or adenocarcinoma) from a cohort of large (at least 20 mm) colorectal adenomas removed by endoscopic resection were subjected to detailed histopathological analysis. The histopathological features in low-grade areas with coexistent adenocarcinoma were reviewed and their diagnostic performance was evaluated. Results: Seventy-four high-grade lesions from 401 endoscopic resections of large adenomas were included. In the low-grade dysplastic areas, a coexistent invasive adenocarcinoma was associated significantly with a cribriform or trabecular growth pattern ( P  < 0.001), high nuclear grade ( P  < 0.001), multifocal intraluminal necrosis (P <  0.001), atypical mitotic figures ( P  = 0.006), infiltrative lesion edges ( P  < 0.001), a broad fibrous band ( P  = 0.001), ulceration ( P  < 0.001), expansile nodules (P <  0.001) and an extensive tumour-infiltrating lymphocyte pattern ( P  = 0.04). Lesions with coexistent invasive adenocarcinoma harboured at least one of these features. The area under the receiver operating characteristic curve (AUROC) for coexistent invasive adenocarcinoma, using frequencies of adverse histopathological factors in low-grade areas, was 0.92. The presence of two or more of these adverse histopathological features in low-grade areas had a sensitivity of 86 per cent and a specificity of 84 per cent for coexistent invasive adenocarcinoma. Conclusion: Several histopathological features in low-grade dysplastic areas of adenomas could be predictive of coexistent adenocarcinoma. Abstract : Histopathological features associated with coexistent invasive adenocarcinoma in large colorectal adenomas have not been described. This study found several histopathological features identified in low grade areas of large adenomas were predictive of the presence of coexistent invasive cancer elsewhere in the lesion. An increasing number of these features is a strong predictor of coexistent invasive adenocarcinoma with an AUROC of 0.92 and ≥2 of these adverse histopathological features in low-grade areas had a sensitivity of 86% and specificity of 84% for coexistent invasive adenocarcinoma.